Uso de la tecnología de virtualización de funciones de red (nfv) en el laboratorio de redes de la universidad técnica de Cotopaxi. - Herrera Molina, Jorge Santiago (2019)
Nowadays the virtualization technology of NFV network functions is the future of telecomunications networks, which allows the research community the possibility of developing new architectures, applications, and evaluating alternatives and service agreements with the objective of achieving a successful with this technology. Despite this, the Information Systems Engineering major at the Technical University of Cotopaxi does not have teaching tolos where students can develop theoretical and practical skills in the technological field of computer networks; Due to this, the computer professionals who graduate from this higher education institution have inadequate knowledge that is why it presents in this research, a network design that serves as a didactic instrument to the network laboratory at the Technical University of Cotopaxi, the necessary requirements for the network design it analyzed, and carried out in 4 stages of a model formulated by the researcher, the results obtained, it was posible to present the data network design proposal that use NFV, with is respective hardware, software device specifications and costs to be implemented in the network laboratory of the Technical University of Cotopaxi, with which students of Information Systems Engineering can know in a theoretical and practical way the virtualization technologies, their creation, management and administration turning them into professionals more trained and placing them in the developers of computer networks.